The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1590/s1516-35982011001200027
|View full text |Cite
|
Sign up to set email alerts
|

Consumo e dinâmica ruminal da fibra em detergente neutro em bovinos em pastejo no período das águas recebendo suplementação com nitrogênio não-proteico e/ou proteína verdadeira

Abstract: RESUMO -Objetivou-se avaliar o efeito de diferentes relações entre proteína verdadeira e nitrogênio não-proteico sobre o consumo e a dinâmica de trânsito e degradação ruminal da fibra em detergente neutro (FDN) da forragem em bovinos em pastejo durante o período das águas. Foram utilizados cinco novilhos mestiços Holandês × Zebu, castrados, com peso corporal inicial de 335±35 kg fistulados no rúmen e no abomaso. Os tratamentos foram: controle (somente pasto); e suplementos com ureia; com 2/3 de compostos nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
6
0
5
Order By: Relevance
“…Therefore, for most production systems, the primary alteration of the diet via supplements must be based on the addition of dietary protein to adjust the energy-to-protein ratio in the diet (Figure 8). In this case, forage intake and fiber digestibility should not change (COSTA et al, 2011b;2011c;LAZZARINI, 2011;RUFINO, 2011;BATISTA, 2012). Increased animal performance has been reported by several authors who used protein/ nitrogen supplementation (including urea as a nitrogen source) in animals grazing on mediumto high-quality forages (ZERVOUDAKIS, 2003;ZERVOUDAKIS et al, 2002;PORTO, 2009).…”
Section: Utilization Of Medium-to High-quality Foragesmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, for most production systems, the primary alteration of the diet via supplements must be based on the addition of dietary protein to adjust the energy-to-protein ratio in the diet (Figure 8). In this case, forage intake and fiber digestibility should not change (COSTA et al, 2011b;2011c;LAZZARINI, 2011;RUFINO, 2011;BATISTA, 2012). Increased animal performance has been reported by several authors who used protein/ nitrogen supplementation (including urea as a nitrogen source) in animals grazing on mediumto high-quality forages (ZERVOUDAKIS, 2003;ZERVOUDAKIS et al, 2002;PORTO, 2009).…”
Section: Utilization Of Medium-to High-quality Foragesmentioning
confidence: 99%
“…However, several reports have suggested that the true influence of nitrogen supplementation seems to be supported by some more complex mechanisms that involve metabolic regulation (COSTA et al, 2011b;2011c;LAZZARINI, 2011;RUFINO, 2011;BATISTA, 2012).…”
Section: Utilization Of Medium-to High-quality Foragesmentioning
confidence: 99%
See 2 more Smart Citations
“…Em experimentos com animais em produção durante o período das águas em condições tropicais, constitui resposta comum a não alteração do consumo de forragem e do coeficiente de digestibilidade da FDN, com concomitante elevação do ganho de peso quando suplementos proteicos (>50% PB) são ofertados (Zervoudakis, 2003;Zervoudakis et al, 2008;Porto, 2009 Tabela 4 -Médias, coeficientes de variação (CV) e níveis descritivos de probabilidade para contrastes (valor-P) para o pH ruminal, concentração de nitrogênio amoniacal ruminal e para as características de utilização dos compostos nitrogenados em função dos tratamentos comportamento, uma vez que o fornecimento de suplementos não alterou o consumo de pasto (Costa et al, 2011). Em grande parte dos trabalhos, a ampliação do ganho de peso (e, por analogia, do balanço de compostos nitrogenados) de animais mantidos em pastos de alta qualidade com suplementação proteica está associada à elevação da concentração de NAR (Zervoudakis, 2003;Moraes et al, 2006;Zervoudakis et al, 2008).…”
Section: Discussionunclassified